Visibility, Attraction, and Typical Person Instagram Endoreser dan Minat Beli Produk Kosmetik Halal Pada Generasi Z di Lombok Timur (Shariah Marketing Analysis) - Titik Husnawati Amini; Muh. Salahuddin (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine whether Visibility and Attraction in Typical Person Endorsers affect the purchase intention of halal cosmetic products in Z-generation in East Lombok, and examine the suitability of sharia in the marketing in question. This research was a survey research with a total sampling of 100 people from Z-generation. Data were collected through questionnaires, and analyzed using multiple linear regression methode. The study found that simultaneously Visibility and Attraction have a significant effect on Purchase Intention. Partially, Visibility has no significant effect on consumer buying interest, while Attraction has a (very) significant effect on consumer buying interest. The majority of respondents in buying halal cosmetic products get products that sometimes match and sometimes do not match what is promoted by the Typical Person Endorser, namely 63 respondents or 63.0% of the total.